2008
DOI: 10.1186/1472-6947-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Handheld computers for self-administered sensitive data collection: A comparative study in Peru

Abstract: Background: Low-cost handheld computers (PDA) potentially represent an efficient tool for collecting sensitive data in surveys. The goal of this study is to evaluate the quality of sexual behavior data collected with handheld computers in comparison with paper-based questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
4
50
0
4
Order By: Relevance
“…A systematic review compared HCDC and paper-and-pencil data collection used in randomized controlled trials and found HCDC to be more time-efficient and better for data management [12]. Furthermore, HCDC can be particularly useful in surveys involving sensitive data such as sexuality, drug use, and other risk behavior [13]. Although limitations were identified by some users, evaluation results from this study suggest that using handheld computers is an acceptable, feasible, and preferred method for data collection in health research in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review compared HCDC and paper-and-pencil data collection used in randomized controlled trials and found HCDC to be more time-efficient and better for data management [12]. Furthermore, HCDC can be particularly useful in surveys involving sensitive data such as sexuality, drug use, and other risk behavior [13]. Although limitations were identified by some users, evaluation results from this study suggest that using handheld computers is an acceptable, feasible, and preferred method for data collection in health research in China.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HCDC data management is more accurate, reliable, and timely compared to paper-and-pencil data collection and manual data entry, and it has been well-accepted by users of such technology [11,12]. HCDC has been commonly used for research in developed countries, and it is increasingly used in the developing world for field data collection [13-15]. …”
Section: Introductionmentioning
confidence: 99%
“…While this approach may have had an impact on response bias due to the presence of an assistant, the much-reduced interaction (compared to a traditional interviewer) will have undoubtedly had a positive impact on the reporting of sensitive responses. Computer-based self-completion also assists in reducing non-sampling errors, such as missing values and incorrect coding, compared to other survey delivery methods (Bernabe-Ortiz et al, 2008).…”
Section: Utilising Technology To Support Self-completionmentioning
confidence: 99%
“…Fletcher, Erickson, Toomey, and Wagenaar (2003) show that although the agreement between methods is very high, it has decreased as forms have increased in length and difficulty. Bernabe-Ortiz et al (2008) compare data concerning sexual behaviour collected with paper forms to data collected with PDA-based forms in Peru. In a first study, each questionnaire was self-administrated in both formats.…”
mentioning
confidence: 99%